2005
DOI: 10.1158/0008-5472.can-05-0420
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adhesion, Invasion, and Metastasis by Antibodies Targeting CEACAM6 (NCA-90) and CEACAM5 (Carcinoembryonic Antigen)

Abstract: CEACAM5 and CEACAM6 are overexpressed in many cancers and are associated with adhesion and invasion. The effects of three monoclonal antibodies targeting different epitopes on these antigens (NH 2 -terminal and A1B1 domains shared by CEACAM5 and CEACAM6 and the A3B3 domain restricted to CEACAM5) were evaluated in migration, invasion, and adhesion assays in vitro using a panel of human pancreatic, breast, and colonic cancer cell lines, and in the GW-39 human colonic micrometastasis model in vivo. MN-3 FabV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
157
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 48 publications
(40 reference statements)
9
157
0
3
Order By: Relevance
“…This result is consistent with the finding that CEACAM6 expression is an early event in human colorectal cancers and plays a role in both early carcinogenesis and subsequent tumor progression (Yasui et al, 2004;Jass, 2005). Previous studies using animal models support that CEACAM6 is functionally important in tumorigenesis, cellular adhesion, growth, invasion, and metastasis, and inhibition of CEACAM6 expression by RNA interference or antibody targeting improved survival of mice with metastases (Ilantzis et al, 2002;Blumenthal et al, 2005). Several experiments in vitro and in vivo demonstrated that CEACAM6 may impede myogenic, adipogenic, neurogenic, and colonic differentiation programs (Duxbury et al, 2004a,b), inhibit anoikis and apoptosis in colon and pancreatic cancer cells, disrupt cell polarization and tissue architecture (Soeth et al, 2001;Duxbury et al, 2004c), enhance liver metastasis (Capurso et al, 2006), increase chemoresistance (Duxbury et al, 2004d), and increase higher incidence of spontaneous colon tumor and lung tumor in a transgenic mouse model (Chan et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with the finding that CEACAM6 expression is an early event in human colorectal cancers and plays a role in both early carcinogenesis and subsequent tumor progression (Yasui et al, 2004;Jass, 2005). Previous studies using animal models support that CEACAM6 is functionally important in tumorigenesis, cellular adhesion, growth, invasion, and metastasis, and inhibition of CEACAM6 expression by RNA interference or antibody targeting improved survival of mice with metastases (Ilantzis et al, 2002;Blumenthal et al, 2005). Several experiments in vitro and in vivo demonstrated that CEACAM6 may impede myogenic, adipogenic, neurogenic, and colonic differentiation programs (Duxbury et al, 2004a,b), inhibit anoikis and apoptosis in colon and pancreatic cancer cells, disrupt cell polarization and tissue architecture (Soeth et al, 2001;Duxbury et al, 2004c), enhance liver metastasis (Capurso et al, 2006), increase chemoresistance (Duxbury et al, 2004d), and increase higher incidence of spontaneous colon tumor and lung tumor in a transgenic mouse model (Chan et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…The roles of these cell membrane proteins in cancer development are well documented. For instance, expression of CEACAMs is associated with poor prognosis in colon cancer (Ishida et al, 2004) and they are considered as a therapeutic target (Blumenthal et al, 2005). Overexpression of biglycan has been identified in pancreatic cancers (Weber et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of different colorectal cell lines to grow in nude mouse spleen and liver models correlates positively with CEA production (33). CEA has emerged as a suitable target antigen for the detection of primary and metastatic colorectal and some other carcinomas (30), and it is presently being evaluated as a possible target for antibody-mediated therapy (34).…”
Section: Discussionmentioning
confidence: 99%